2017
DOI: 10.1007/s11906-017-0742-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Paced Breathing for Treatment of Hypertension

Abstract: Asking patients to carry out paced breathing sessions unaccompanied by a personal coach or unaided by a device may be unfeasible. Among proposed breathing techniques, RESPeRATE is a US Food and Drug Administration-certified device that assists slow breathing. In this review, we consider the mechanisms through which guided breathing mechanisms may impact on blood pressure control and alternative techniques. Guided breathing techniques along with lifestyle therapies may be helpful as a first step for patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 74 publications
0
21
0
1
Order By: Relevance
“…Biobehavioral therapies usually result in positive health change, and studies have shown an impact on those diagnosed with hypertension (Cernes & Zimlichman, 2017; Herakova et al, 2017; Jones et al, 2015; Landman et al, 2014; Li et al, 2018; Mahtani et al, 2016; Van Hateren et al, 2014; Zhang et al, 2016). BF incorporates technology and self-management and can help to meet young adults’ health promotion needs (Lehrer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Biobehavioral therapies usually result in positive health change, and studies have shown an impact on those diagnosed with hypertension (Cernes & Zimlichman, 2017; Herakova et al, 2017; Jones et al, 2015; Landman et al, 2014; Li et al, 2018; Mahtani et al, 2016; Van Hateren et al, 2014; Zhang et al, 2016). BF incorporates technology and self-management and can help to meet young adults’ health promotion needs (Lehrer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of researches authors hold the opinion concerning importance of training of the person in full breath and its any regulation (Szabo & Kocsis, 2017;Tavares, de Paula Vidigal, Garner, de Abreu, & Valenti, 2017;Cernes & Zimlichman, 2017;Todd, Walsted, Grillo, Menzies-Gow, & Hull, 2018). At the same time in special literature, there are a large number of results of the experimental studies demonstrating the advantage of a hypoxia .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is generally accepted that PIH is characterized by sympathetic overactivity ( 23) and there is evidence that yoga and SDB decrease sympathetic dominance and increase parasympathetic activity (24,25). SDB has also been shown to reduce total peripheral resistance (26), combating the increase in total peripheral resistance associated with PIH (27).…”
Section: Introductionmentioning
confidence: 99%